"Yes, I Can!" adult literacy campaign - Wise, Jenny (ADA Dataverse, 2020)
This research examined the impact of the ‘Yes, I Can!’adult literacy campaign as a place based justice reinvestment initiative, using both qualitative and quantitative approaches. Interviews conducted with 22 key informants working as service providers or criminal justice system employees within (or previously located in) Bourke and Enngonia indicated that the ‘Yes, I Can!’ campaign improved the experiences and interactions of participating community members with the criminal justice system in at least three ways. It helped to alleviate illegal driving practices; it reduced contacts with the law for failure to respond to official documentation; and it improved their interactions with law enforcement officials. There were also significant benefits in terms of increased confidence to access legal advice and other services.